Long-lived coralline alga records multidecadal variability in Labrador Sea carbon isotopes - Hou, Alicia; Halfar, J.; Adey, W.; Wortmann, U. G.; Zajacz, Z.; Tsay, A.; Williams, B.; Chan, P. (Chemical geology, 2019)
While the recent decline in the δ13C composition of oceanic dissolved inorganic carbon (DIC) can be attributed to increasing anthropogenic CO2 emissions (13C Suess effect), the causes of natural variability in the δ13C of oceanic DIC (δ13CDIC) are far less understood. Unfortunately, instrumental oceanic DIC measurements are not available prior to the 1970s, prohibiting the observation and study of long-term variability in oceanic carbon isotope dynamics. Thus, in order to identify the main driving forces of changes in oceanic δ13CDIC, multicentury carbon isotope time series that extend from the present into the preindustrial period are required. Such time series may be extracted from the carbonate skeletons of long-lived marine organisms, which have been shown to be robust recorders of fluctuations and trends in oceanic δ13CDIC. In this study, we use an annually-banded coralline alga live-collected from the Labrador shelf to generate a 266-year time series of δ13CDIC changes in the Labrador Sea. Our results indicate that from the 1960s onwards, the rate of δ13CDIC decline in the Labrador Sea slightly exceeds the rate of δ13C decline in the atmosphere, providing support for the enhanced CO2 uptake ability of the Labrador Sea. In addition, the detrended algal δ13C time series displays multidecadal variability with typical Atlantic Multidecadal Oscillation (AMO) frequencies. We show that prior to the late 1980s, algal δ13C compositions significantly correlate with regional sea ice cover (SIC) variability, post-1850 instrumental, reconstructed AMO indices, and solar variability. We speculate that these low-frequency oscillations in δ13C reflect changes in marine primary productivity modulated by a mechanism involving solar changes, the AMO and SIC variability. Our algal carbon isotope time series suggests that while the anthropogenic Suess effect has influenced Labrador Sea δ13CDIC since the 1960s, its influence may have been obscured by the effects of natural climatic variability up until the late 1980s.
Available online 21 February 2018
Gesehen am 06.07.2021